Exploring the Effects of Stellar Magnetism on the Potential Habitability of Exoplanets - Atkinson, Anthony S.; Alexander, David; Farrish, Alison O. (The Astrophysical journal, 2024)
Considerable interest has centered on Earth-like planets orbiting in the circumstellar habitable zone (CHZ) of its star. However, the potential habitability of an exoplanet depends upon a number of additional factors, including the presence and strength of any planetary magnetic field and the interaction of this field with that of the host star. Not only must the exoplanet have a strong enough magnetic field to shield against stellar activity, but it must also orbit far enough from the star to avoid direct magnetic connectivity. We characterize stellar activity by the star’s Rossby number, Ro, the ratio of stellar rotation rate to convective turnover time. We employ a scaled model of the solar magnetic field to determine the star’s Alfvén radius, the distance at which the stellar wind becomes super-Alfvénic. Planets residing within the Alfvén surface may have a direct magnetic connection to the star and therefore not be the most viable candidates for habitability. Here, we determine the Rossby number of a sample of 1053 exoplanet-hosting stars for which the rotation rates have been observed and for which a convective turnover time can be calculated. We find that 84 exoplanets in our sample have orbits which lie inside the CHZ and that also lie outside the star’s Alfvén surface: 34 of these have been classified as terran (11) or superterran (23) planets. Applying the Alfvén surface habitability criterion yields a subset of the confirmed exoplanets that may be optimal targets for future observations in the search for signatures of life.